The relationship between Islamic work ethics, employee engagement and organizational citizenship behavior among Malaysian civil servants - Zulhusni, Mohamad Rashid (2020)
Civil servants have a vital role to play in the execution of various national economic transformation plans in realizing Vision 2020. Civil servants who possess OCB that voluntarily transcend beyond their task performance expectation are crucial to enhance government delivery efficiency to the public. Islamic work ethics has been widely embraced by the majority of civil servants in this country and has a significant effect on various workplace behaviours. This study aims to determine the mediation effect of employee engagement on the relationship between Islamic work ethics and OCB among Malaysian Civil Servants. Based on the theoretical framework, four main hypotheses were developed, and statistically tested. The sample size suggested are 256 employees were drawn from Human Resources Department from Unfederated Malay States (UFMS) namely Johor, Kedah, Kelantan and Terengganu using a stratified random sampling procedure. Using a survey method, a total of 153 state civil servants have participated in this study. The hypotheses of the study were tested by applying multiple regression and parallel mediation test. In brief, the results indicated a positive relationship between some dimensions of IWE and OCB, between IWE and EE and between EE and OCB. Similarly, a negative relation between some aspects of IWE and OCB, between IWE and EE and between EE and OCB. In addition, the study found that the EE mediates the relationship between IWE and OCB. Hence, this study was able to expand the boundary of existing literature. Finally, the findings from this study provided has a few managerial implications to government agencies and policymakers in ensuring efficient public service delivery.